2020
DOI: 10.3390/microorganisms8020217
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Obligate Mixotrophic Methanogen That Represents the Major Population in Thermophilic Fixed-Bed Anaerobic Digesters

Abstract: Methanothermobacter Met2 is a metagenome-assembled genome (MAG) that encodes a putative mixotrophic methanogen constituting the major populations in thermophilic fixed-bed anaerobic digesters. In order to characterize its physiology, the present work isolated an archaeon (strain Met2-1) that represents Met2-type methanogens by using a combination of enrichments under a nitrogen atmosphere, colony formation on solid media and limiting dilution under high partial pressures of hydrogen. Strain Met2-1 utilizes hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…0.2%), from the same biofilm, and genomic analyses have revealed that this methanogen has Codh/Acs [7]. In a subsequent study, archaeal strains that represent Met2 and Met20 were isolated, and growth tests have demonstrated that Met20 is able to grow autotrophically on hydrogen and carbon dioxide, while Met2 requires acetate in addition to hydrogen and carbon dioxide [8]. According to the catabolic pathways illustrated in Figure 1, it is likely that Codh/Acs-deficient methanogens utilize hydrogen and carbon dioxide only for conserving energy by methanogenesis, while acetate is activated by acetyl-CoA synthase and/or acetate kinase plus phosphotransacetylase and solely used as a carbon source.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…0.2%), from the same biofilm, and genomic analyses have revealed that this methanogen has Codh/Acs [7]. In a subsequent study, archaeal strains that represent Met2 and Met20 were isolated, and growth tests have demonstrated that Met20 is able to grow autotrophically on hydrogen and carbon dioxide, while Met2 requires acetate in addition to hydrogen and carbon dioxide [8]. According to the catabolic pathways illustrated in Figure 1, it is likely that Codh/Acs-deficient methanogens utilize hydrogen and carbon dioxide only for conserving energy by methanogenesis, while acetate is activated by acetyl-CoA synthase and/or acetate kinase plus phosphotransacetylase and solely used as a carbon source.…”
Section: Resultsmentioning
confidence: 94%
“…It is however also conceivable that other organic compounds may support the growth of some Codh/Acs-deficient methanogens, and this should be addressed in future studies. It is also noteworthy that the growth of Met2 was slower than Met20 even in the presence of acetate [8], suggesting that Met2 may have some advantages other than growth rate over Met20, which facilitate Met2 to constitute dominant populations in anaerobic digesters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation